Measuring dynamic changes in cAMP using fluorescence resonance energy transfer. - Evellin, S; Mongillo, M; Terrin, A; Lissandron, V; Zaccolo, M (2004)
cAMP is a ubiquitous second messenger that controls numerous cellular events including movement, growth, metabolism, contraction, and synaptic plasticity. With the emerging concept of compartmentalization of cAMP-dependent signaling, a detailed study of the spatio-temporal intracellular dynamics of cAMP is required. Here we describe a new methodology for monitoring fluctuations of cAMP in living cells, based on the use of a genetically encoded biosensor. The regulatory and catalytic subunits of the main cAMP effector, the protein kinase A (PKA), fused with two suitable green fluorescent protein (GFP) mutants is used for measuring changes in fluorescence resonance energy transfer (FRET) that correlate with changes in intracellular cAMP levels. This method allows the study of cAMP fluctuations in living cells with high resolution both in time and in space.